Technology and Design at Key Stage 3: Perceptions of challeng - Gibson, Ken (Design and Technology Education: An International Journal, 2007)
The Educational Reform (Northern Ireland) Order (1989) created Technology and Design as a new and compulsory component of the curriculum for all pupils at Key Stage 3. This research investigates the range of challenge that the teachers of Technology and Design perceive to exist for them as they seek to deliver this subject.  A questionnaire was constructed and forwarded to all teachers (578) of Technology and Design in Northern Ireland and analysis of the 220 responses received revealed a number of significant factors. These factors were further explored using semi-structured interviews with 24 teachers.  Three main issues are identified and discussed. Firstly, issues related to the Management of Technology and Design and its implementation in the classroom are considered. The challenges presented here relate to the management of teaching and learning within the subject; for example project work, health and safety, resources and staff support, both technical and financial. Other challenges focus upon class size, subject time allocation, recruitment and subject groupings, assessment and generally ‘keeping things on track’. The second group of challenges relates to Development within Technology and Design and these are focussed upon the evolving nature of the subject and the need to keep up-to-date with the ever-changing subject content. Finally the actual teaching of the subject and some of the challenges involved are considered. Technology and Design is perceived to be an important and indeed a very valuable subject but it presents many challenges to the teachers involved.